Seasonal water source patterns in a northern Arizona pine forest - Kerhoulas, Lucy P.; Umstattd, Nicolas; Koch, George W. (Frontiers in Forests and Global Change, 2023)
The relationships among stand density and seasonal plant water source patterns in ponderosa pine (Pinus ponderosa) forests are important for informed management decisions in a bimodal climate with increasing variability in winter and monsoon precipitation inputs. Winter precipitation recharges soil moisture, yet it has declined over the past 20 years in the southwestern United States, and monsoon precipitation is becoming more variable in both magnitude and timing. Near Flagstaff, Arizona in August 2013 (monsoon), October 2013 (post-monsoon), and May 2014 (post winter snow melt), we measured soil moisture, soil water dD at five depths, and xylem water dD in Muhlenbergia montana (a perennial C4 grass), Festuca arizonica (a perennial C3 grass), and P. ponderosa seedlings (< 2 yrs old), saplings (2-5 cm basal diameter), and mature trees (> 60 cm diameter at breast height) in treated (thinned and burned) and untreated (no thinning, no burning) stands. We found that soil moisture was higher at all soil depths in treated stands in May, after snow melt, and this pattern persisted through August in the deepest soil (60 cm). We also found that, in all sampling months, dD in xylem of grasses and pine seedlings indicated use of shallower soil water than for pine saplings and mature trees, presumably due to differences in rooting depths. Additionally, in August, dD in xylem of pine saplings and mature trees indicated greater reliance on a deeper water source in untreated stands than in treated stands, likely due to greater competition for shallow water in untreated stands. Our isotopic data indicate that grasses and seedlings used predominantly monsoon water in August and October, while pine saplings and mature trees used predominantly winter water during all sampling months. Importantly, our data indicate that regenerating trees (seedlings and saplings) used both winter and monsoon seasonal water sources, supporting an increasingly important role for monsoon precipitation if winter precipitation inputs continue to decline. Collectively, these findings demonstrate that management actions can benefit forests via increased soil moisture, that overstory trees rely predominantly on winter precipitation, and that monsoon precipitation is important for herbaceous species and younger, regenerating overstory trees.